A Qualitative Comparison of the Reactivities of 3,4,4,5-Tetrachloro-4H-1,2,6-thiadiazine and 4,5-Dichloro-1,2,3-dithiazolium Chloride - Andreas S. Kalogirou (Molecules, 2015)
The high yielding transformations of 3,4,4,5-tetrachloro-4H-1,2,6-thiadiazine into 3,5-dichloro-4H-1,2,6-thiadiazin-4-one (up to 85%) and 2-(3,5-dichloro-4H-1,2,6-thiadiazin-4-ylidene)malononitrile (up to 83%) have been investigated and compared to the analogous transformations of the closely-related 4,5-dichloro-1,2,3-dithiazolium chloride (Appel’s salt) into 4-chloro-5H-1,2,3-dithiazol-5-one and 2-(4-chloro-5H-1,2,3-dithiazol-5-ylidene)malononitrile. Furthermore, cyclocondensation of 3,4,4,5-tetrachloro-4H-1,2,6-thiadiazine with 2-aminophenol and 1,2-benzenediamines gave fused 4H-1,2,6-thiadiazines in 68%–85% yields.